A thermally reversible healing EPDM based elastomer with higher tensile properties and damping properties. Issue 5 (12th September 2020) - Xiong, Chengtian; Li, Xiaoqing; He, Hezhi; Xue, Bin; Wang, Yi; Li, Jiqian; Zhu, Zhiwen
Abstract: Due to the disadvantages of lower tensile strength and fracture toughness, the widely application of Ethylene‐propylene‐diene‐monomer rubber (EPDM) has been limited. In this study, a thermally reversible healing EPDM based elastomer with H‐bonding and Zn‐based‐bonding dynamic cross‐link network was prepared. The influence of mole ratio of ATA/MAH on tensile strength and fracture energy of mEPDM0 ‐xATA was investigated. The results showed that increasing the content of ATA brings about a gradual improvement in tensile strength of the mEPDM0 ‐xATA. Especially when the mole ratio of ATA/MAH is 1, the fracture energy of mEPDM0 ‐ATA is dramatically enhanced to 33.9 MJ/m 3, which is best among the ratios studied in our research. After curing, the effect of ZnCl2 content on tensile strength and fracture energy of mEPDM‐ATA‐nZn was also studied. Meanwhile, the uniaxial cyclic loading‐unloading tensile test was used to study the viscous damping properties of mEPDM‐ATA‐0.4Zn, which showed reversible repair properties after heat treatment. The results of dynamic rheological measurement showed that the damping properties were improved. Abstract : In this work, we introduced H‐bonding and Zn‐based‐bonding through ATA functional groups to form a thermoreversible dynamic physical cross‐linking network. When the ATA/MAH molar ratio is 1.0, the fracture energy of mEPDM0 ‐ATA is dramatically enhanced to 33.9 MJ/m 3, which is best among the ratios studied in our research. Due to the formation of dynamic cross‐link network, the damping properties were improved.